PERSEPSI PASIEN DI RSUD WANGAYA KOTA DENPASAR BERBASIS APLIKASI PENDAFTARAN ONLINE (APDOL) - Candradewi, Anak Agung Sagung Oka Nur; Januraga, Pande Putu (ARCHIVE OF COMMUNITY HEALTH; Vol 10 No 3 (2023): Desember 2023, 2023)
Online Registration Application (APDOL) as an alternative way of Wangaya Hospital Denpasar City in overcoming the problem of handling patient queues. Which began to be applied at the Wangaya Hospital, Denpasar City in 2018. This study aims to describe the patient's perception of the use of APDOL use at the Wangaya Hospital, Denpasar City. This study is a qualitative descriptive study conducted in February-June 2022. The informants in this study consisted of 20 visiting patients at Wangaya Hospital. Data were collected by semi-structured interviews. The data analysis technique was carried out with three activities, namely data reduction, data presentation, and drawing conclusions. The results of this study indicate that patients who use APDOL give a good response to the presence of APDOL in dealing with queuing problems at Wangaya Hospital. The inhibiting factor of the use of APDOL is the lack of socialization by the hospital. While the supporting factors for the existence of APDOL are the ease of using APDOL, increasing effectiveness, and flexible usage time. It is recommended that Wangaya Hospital conduct on going socialization to introduce APDOL to patients. Keywords: Online Registration Application (APDOL), Application Usage Utilization, Perception, Technology Acceptance Model (TAM).